2017
DOI: 10.1590/0104-07072017005460015
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated to Subjective Wellbeing in Older Adults

Abstract: Objective: identify the factors associated with subjective wellbeing in older adults. Method: analytical, cross-sectional study developed in Chile. The sample consisted of 20,351 seniors, who answered a question on overall life satisfaction in the National Socio-Economic Survey, 2011. Subjective wellbeing was correlated with health, demographic and social indicators. Comparisons of averages, correlations and regressions were applied using the software Statistical Package for the Social Sciences 20. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1
12

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 11 publications
0
6
1
12
Order By: Relevance
“…Health predominates among other predictors of subjective well-being. The relationship between health and well-being has also been found in multiple studies [19,22,77,78]. Menec and Nowicki [39] found that perceived health had significant positive effects on the physical environment, social environment, opportunities for participation, and transport options.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Health predominates among other predictors of subjective well-being. The relationship between health and well-being has also been found in multiple studies [19,22,77,78]. Menec and Nowicki [39] found that perceived health had significant positive effects on the physical environment, social environment, opportunities for participation, and transport options.…”
Section: Discussionmentioning
confidence: 78%
“…For them, not needing help to carry out the daily life activities is also a clear predictor of higher subjective well-being. Functional limitations of older people have been found to be associated with it [ 61 , 78 ] and some studies have corroborated how this affects women more [ 61 ]. These results may be related to the importance of living together for men, but not for women.…”
Section: Discussionmentioning
confidence: 99%
“…The Domain 11-Security/Protection, the diagnosis "Suicide risk" was identified in an elderly woman who manifested having pessimistic thoughts about her future, including suicidal ideas, despite having a very healthy lifestyle; and the diagnosis "Risk of falls" in 30 elders by age equal to or greater than 65 years old, five reported a history of falls, one had the use of assistive devices (stick), three lived alone, 29 had the risk of alteration in the blood sugar level, two suffered from arthritis and one had deterioration of balance; DM2 constitutes a risk of falls in 27.37%. 24 The elaboration of the nursing diagnoses in this work proved that a nursing diagnosis follows next to others (named by NANDA-I as a syndrome), so it is better to address them together. 12 As an evidence we have the following diagnoses: Risk of unstable blood sugar level, which includes the following diagnoses: Overweight, Obesity, Poor knowledge, Sedentary lifestyle, Ineffective health management and Non-compliance; likewise, the diagnosis Deterioration of the regulation of mood includes the diagnosis Suicide risk; and in the same context the diagnosis Risk of frailty syndrome of the elderly includes the diagnosis Risk of falls.…”
Section: /12mentioning
confidence: 73%
“…SWB is associated with elements such as the degree of social integration, support networks, and professional activities (Dolan & White, 2007 ; Herrera et al, 2014 ; Silva, 2014 ) as well as social contacts, including family and friends (Kamp Dush & Amato, 2005 ; Lara et al, 2019 ). In addition, older adults with partners (Kamp Dush & Amato, 2005 ), a higher level of education (San Román et al, 2017 ), and high incomes have a higher status and stimulation levels as well as a higher well-being than those without such resources (Barnes et al, 2006 ; Lyons, 2009 ).…”
Section: Previous Studies On Older Adults’ Well-beingmentioning
confidence: 99%